Efficient Electroluminescence from Excimers of 1, 3, 6, 8‐Tetrakis(3, 5‐dimethylphenyl)pyrene. Issue 2 (19th November 2012) - Chang, Zhengfeng; Ye, Shanghui; He, Bairong; Bei, Zirong; Lin, Liya; Lu, Ping; Chen, Bin; Zhao, Zujin; Qiu, Huayu
Abstract Excimers are generally considered as detrimental to OLEDs. For pyrene‐based chromophores, however, this is not always true. In this contribution, two new methylated tetraphenylpyrenes, 1, 3, 6, 8‐tetra‐o‐tolylpyrene (TTPy) and 1, 3, 6, 8‐tetrakis(3, 5‐dimethylphenyl)pyrene (TDMPPy), were synthesized through Suzuki coupling reactions. TDMPPy absorbs and emits light at longer wavelengths than TTPy due to its more planar conformation and thus better conjugation. TDMPPy is prone to excimer formation, thus leading to a strong bathochromic shift (84 nm) in the photoluminescence spectrum of its film. TDMPPy exhibits efficient electroluminescence originating from pyrene excimers, affording a maximum luminance of 26 670 cd m−2 and a current efficiency as high as 10.8 cd A−1 in a non‐doped OLED (ITO/PEDOT:PSS (50 nm)/NPB (30 nm)/TDMPPy (30 nm)/TPBI (40 nm)/Ca:Ag).